Social protection of the self-employed in old age in the EU - Thais Guerrero Padrón (Stanovništvo)
In most European Union (EU) Member States, self-employed individuals receive, on average, lower retirement pensions than employees. Furthermore, the number of self-employed pensioners is lower, and there is a significant proportion of self-employed workers in the EU who are not entitled to a retirement pension. The situation is even more delicate for the new self-employed, as their mode of labour market participation, career trajectory, and the income level they reach can potentially compromise their future pension prospects. This paper analyses the position of self-employed workers within national social security systems, with a particular focus on their methods of contribution and the consequential impact on their ability to access adequate retirement pensions as a form of replacement income, thus avoiding the risk of poverty and ensuring a decent standard of living in old age. In this area, the Member States and the EU interact within the framework of their respective competences, with the manifest aim of improving the social protection of self-employed workers in their senior years.